Ribonuclease L is not critical for innate restriction and adaptive immunity against Friend retrovirus infection - Li, Sam X. (2013)
Ribonuclease L (RNase L) is a Type I Interferon regulated factor that can significantly inhibit retroviruses in vitro and may activate cytoplasmic sensing pathways to augment adaptive immunity. However, the antiretroviral activity of RNase L remains to be validated in vivo. We investigated the role of RNaseL in counteracting Friend retrovirus (FV) infection relative to a well-described restriction factor, Apobec3. C57BL/6 wild-type (WT) and RNaseL knock-out (KO) mice exhibited similar acute FV infection levels despite significant transcriptional induction of Oligoadenylate Synthetase 1, which produces activators of RNase L. Apobec3 KO mice showed higher FV infection levels relative to WT mice, but deletion of RNaseL in Apobec3 KO mice did not augment FV infection. Moreover, RNaseL did not influence FV-specific IgG responses and recovery from viremia by 28 days post-infection. The results suggest that RNase L is not an evolutionarily-conserved host defense mechanism to counteract retroviruses in vivo.